Polarization and the Nationalization of State Legislative Elections. Issue 5 (September 2019) - Zingher, Joshua N.; Richman, Jesse
The electoral fortunes of state parties are partly shaped by the positions adopted by national parties. This creates the potential dilemma: The position that is best for the national party might be too extreme for the electorate in some states. Some state parties attempt to address this problem by adopting more moderate positions than their national-level counterparts. We argue that the efficacy of state party moderation hinges on the degree of polarization at the national level. We develop theory and examine empirical evidence that higher relative polarization at the national level exacerbates the degree to which national party positions and loyalties determine outcomes in U.S. state elections. When relative national polarization is high, we find evidence that state legislative election outcomes are determined by states' orientations toward the national parties rather than the positions taken by state legislative parties.